A influência da urbanização na formação de ilhas de calor na cidade de Boa Vista-RR - Pereira, Yanne Cristhine Castro (2018)
Urbanization contributes to the increased formation of heat islands in the cities, caused by changes in the natural surface, paving, land use, typologies of buildings, materials used and the human activities undertaken. The aim of this present study is to investigate the relationship between the urban space built and the temperature variation and how does the urbanization influences in the formation of the urban climate and possible occurrence of heats islands in Boa Vista city. For both were analysed the relationship between the physical characteristics and thermal variation using temperature data collected in five fixed points in the urban environment and in the surroundings of the city according to the characteristics of surface considering the type of use and occupation of land in surroundings. Based on the mappings and multitemporal analysis using images and data from years 1985, 2005 and 2017 of remote sensing satellite Landsat 5 in the bands 3, 4, 5 and Landsat 8 in 4, 5, 6 in Red, Green and Blue (RGB) to preparation of map of the use and occupation of the soil and of the Landsat satellite 5 in band 6 and the Landsat 8 in band 10 of the thermal infrared band to making the map of the apparent thermal temperature, we have been verified the effects of urban sprawl on the variation of the temperature and the identification of the existence of heat islands in the city. The results support the existence of locations in the urban space built or altered with higher temperatures than in the surrounding areas with the vegetation and natural surface still conserved. According to the characteristics of the surface the use of the soil and the vegetation, multitemporal analysis showed that, as urbanization grew up west of the city areas that exhibit higher temperatures also increased which confirms that urbanization has a significant effect on temperature variation in urban space and in the formation of heat islands in the Boa Vista city.